2014
DOI: 10.4049/jimmunol.1400749
|View full text |Cite
|
Sign up to set email alerts
|

Early Lymphoid Responses and Germinal Center Formation Correlate with Lower Viral Load Set Points and Better Prognosis of Simian Immunodeficiency Virus Infection

Abstract: We have investigated the dynamics of germinal center (GC) formation in lymphoid tissues following acute SIV infection. SIV induces a marked follicular hyperplasia, associated with an aberrant accumulation of non-proliferating TFH cells within GCs, but with an abundance of cells producing IL-21, demonstrating that the mechanisms involved for these 2 events appear independent. IL-21 stimulated TFH cells are considered a critical element for GC formation, a physiological process that seems dysregulated and excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 36 publications
6
44
0
2
Order By: Relevance
“…The dynamics of Tfh cell induction in acute HIV‐1 infection have not been precisely determined, but LN GCs containing proliferating Tfh cells are present in macaques by day 14 post‐SIV infection,168, 169 suggesting rapid induction of a Tfh cell response following infection.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…The dynamics of Tfh cell induction in acute HIV‐1 infection have not been precisely determined, but LN GCs containing proliferating Tfh cells are present in macaques by day 14 post‐SIV infection,168, 169 suggesting rapid induction of a Tfh cell response following infection.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…Antigen-activated B cells making contact with a specialized subset of CD4 + T cells, called T follicular helper cells (T FH ), can enter the germinal centers (GCs) to undergo to somatic hypermutation and affinity maturation (4). T FH home to B follicles and GC (5) (6, 7) (8, 9) by up-regulating the chemokine (C-X-C motif) receptor 5 (CXCR5) and down-regulating the chemokine (C-C motif) receptor 7 (CCR7) (10)(5)(6). T FH express high levels of programmed death 1 (PD-1), inducible co-stimulator (ICOS), and Bcl-6, a master transcriptional regulator that orchestrates T FH differentiation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Production of the IL-21 cytokine by T FH is significantly reduced during HIV/SIV infection, possibly affecting GC homeostasis and the development of effective humoral responses to the virus (37). The HIV/SIV associated changes in T FH number and function may contribute to the impairment of B-cell responses (9)(36)(38), however other studies have found associations between the levels of functional T FH and broadly neutralizing antibodies in chronic HIV patients (39). While the relative role of T FH in HIV pathogenesis needs further investigation, it would be important to understand the molecular and cellular mechanisms that regulate T FH expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, there is also generalized lymphoid damage characterized by a reduction in GC size and number, which is accompanied by fibrosis, and follicular involution with nearly complete destruction of the fibroblastic reticular cell network (8, 9). These features have been shown to gradually result in an inability to mediate antibody production and generate effective antigen-specific T cell responses in late stages of infection, contributing to AIDS (1012). It is reported that CXCR5+ Tfh in lymph nodes cells accumulate in SIV/HIV infection (1315), so these Tfh cells are thus thought to be dysregulated due to infection, resulting in inadequate B-cell help and subsequent impairment of B cell responses (16, 17).…”
Section: Introductionmentioning
confidence: 99%